Simultaneous real-time imaging of the ocular anterior segment including the ciliary muscle during accommodation - Shao, Yilei; Tao, Aizhu; Jiang, Hong; Shen, Meixiao; Zhong, Jianguang; Lu, Fan; Wang, Jianhua (Biomedical optics express, 2013)
We demonstrated a novel approach of imaging the anterior segment including the ciliary muscle using combined and synchronized two spectral domain optical coherence tomography devices (SD-OCT). In one SD-OCT, a Complementary Metal-Oxide-Semiconductor Transistor (CMOS) camera and an alternating reference arm was used to image the anterior segment from the cornea to the lens. Another SD-OCT for imaging the ciliary muscle was equipped with a light source with a center wavelength of 1,310 nm and a bandwidth of 75 nm. Repeated measurements were performed under relaxed and 4.00 D accommodative stimulus states in six eyes from 6 subjects. We also imaged dynamic changes in the anterior segment in one eye during accommodation. The biometry of the anterior segment and the ciliary muscle was obtained. The combined system appeared to be capable to simultaneously real-time image the biometry of the anterior segment, including the ciliary muscle, in vivo during accommodation.